How to speak dog! - Whitehead, Sarah (New York : Scholastic, 2008)
Describes how to read a dog's body language, explains how to effectively train a dog, and offers advice for what to expect as a pet owner and ideas for games both dogs and owners will enjoy.
Includes index.
7 - 10 years
Keywords: Dogs -- Behavior; Dogs -- Training; Human-animal communication; Dogs -- Habits and behavior